Scoping Review: Intrumen Pengkajian Cancer Related Fatigue Pasca Pengobatan Kanker - Adawiyah, Robiatul; Fauji, Achmad; Rahmah, Nur Miladiyah; Astuti, Puji (Faletehan Health Journal, 2024)
Cancer is a serious disease that causes issues such as fatigue, making the assessment of fatigue using high-quality instruments critically important. Reviewing instruments widely used by healthcare professionals is crucial to optimize nursing care. The aim of this study was to identify fatigue assessment instruments used for post-treatment cancer patients in studies from the last ten years. This study employed a scoping review design with the keywords “Assessment Cancer Related Fatigue and Treatment” and included screening using the PRISMA flow. The study results indicated that 10 articles used 9 different assessment instruments, including the Piper Fatigue Scale, Multidimensional Fatigue Inventory, Fatigue Assessment Questionnaire, Functional Assessment of Cancer Therapy Fatigue, PROMIS Fatigue Short Form 7a, Functional Assessment of Chronic Illness Therapy Fatigue Scale, Fatigue Severity Scale, Cancer Fatigue Scale, and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire. The most frequently used instruments were the Piper Fatigue Scale in 3 articles and the Multidimensional Fatigue Inventory in 2 articles.